PENGARUH PROPORSI SINGKONG DAN LOBAK (Raphanus sativus L.) TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK HASHBROWN SINGKONG - Pringgowati, Suesti Lilis; Surjoseputro, Sutarjo; Setijawati, Erni (Jurnal Teknologi Pangan dan Gizi, 2017)
Hashbrown is a product of potato that is made by shredding the potatoes, cutting into thin blocks, cut into dice, or pressed using rice potatoes then fried. The characteristic of Hash browns are soft in texture, moist and compact. In general, hash browns are made from potatoes. In this study, hash browns are made from cassava which has high carbohydrate levels, neutral aroma, light yellow colouring resembling potatoes and a savoury flavour. Hash brown product that just use cassava as a main ingredient, do not meet the characteristics of hash browns in general, which is not moist, so the addition of horseradish was necessary. Horseradish (Raphanus sativus L.) is a white tuber vegetable with 7.1% inulin. Inulin is a natural polimer formed from fructose units with a terminal glucose group. The role of inulin in hash browns is to provide moistness. Different concentration of the horseradish can give different characteristics to the taste, texture and ease of swallowing on hash brown product. The study design used is non-factorial RAK (Randomised Complete Block Design). Factors studied were concentration of horseradish consisting of 9 (nine) standard of treatments in the form of 0%(b/b); 5%(b/b);10%(b/b); 15%(b/b); 20%(b/b); 25%(b/b); 30%(b/b); 35%(b/b); 40%(b/b), with 3 replication. The parameters included physicochemical properties (moisture, fat content, absorption of oil, hardness and texture cohesiveness,) and the organoleptic properties (preference for taste, ease to swallow). The studied show that the proportion of cassava:horseradsih (70:30%) was the best, with water content 55,83%, oil absorption 32,84%, hardness 3,13 kg and cohesiveness 0,36 g, organoleptic proporties for aroma (5,51), taste (6,05), and swallowing (6,29) with standart score 1-9.